Iron Metabolism Contributes to Prognosis in Coronary Artery Disease: Prognostic Value of the Soluble Transferrin Receptor Within the AtheroGene Study. Issue 9 (5th May 2020) - Weidmann, Henri; Bannasch, Johannes H.; Waldeyer, Christoph; Shrivastava, Apurva; Appelbaum, Sebastian; Ojeda‐Echevarria, Francisco Miguel; Schnabel, Renate; Lackner, Karl J.; Blankenberg, Stefan; Zeller, Tanja; Karakas, Mahir
Abstract : Background: Coronary heart disease is a leading cause of mortality worldwide. Iron deficiency, a frequent comorbidity of coronary heart disease, causes an increased expression of transferrin receptor and soluble transferrin receptor levels (sTfR) levels, while iron repletion returns sTfR levels to the normal physiological range. Recently, sTfR levels were proposed as a potential new marker of iron metabolism in cardiovascular diseases. Therefore, we aimed to evaluate the prognostic value of circulating sTfR levels in a large cohort of patients with coronary heart disease. Methods and Results: The disease cohort comprised 3423 subjects who had angiographically documented coronary heart disease and who participated in the AtheroGene study. Serum levels of sTfR were determined at baseline using an automated immunoassay (Roche Cobas Integra 400). Two main outcomes were considered: a combined end point of myocardial infarction and cardiovascular death and cardiovascular death alone. During a median follow‐up of 4.0 years, 10.3% of the patients experienced an end point. In Cox regression analyses for sTfR levels, the hazard ratio (HR) for future cardiovascular death and/or myocardial infarction was 1.27 (95% CI, 1.11–1.44, P <0.001) after adjustment for sex and age. This association remained significant (HR, 1.23; 95% CI, 1.03–1.46, P =0.02) after additional adjustment for body mass index, smoking status, hypertension, diabetes mellitus, dyslipidemia, C‐reactive protein, and surrogates of cardiac function, size of myocardial necrosis (hs‐Tnl), and hemoglobin levels. Conclusions: In this large cohort study, sTfR levels were strongly associated with future myocardial infarction and cardiovascular death. This implicates a role for sTfR in secondary cardiovascular risk prediction.